Development of the Educational Sport in Indonesia: The Policy Study Based on the Law of National Sports System - Ma’mun, Amung (ASPENSI, 2015)
ABSTRACT: The National Sports System Law in 2005 stated that the scope of sports system in Indonesian is divided into three components, they are: Educational Sport, Recreational Sport, and Competitive Sport. Like it or not, there has been still a bias in the way peoples gave meaning of the sports in the planning document, which is irrelevant with the true meaning purported by the law; and in which it is also still meant that the sports should be directed to the cultivation of the high performance solely. This is definitely inaccurate meaning for which the real meaning of educational sport has its own goal and different targets, giving children broader opportunities to expand and explore their own potentialities. The policy to develop educational sport is supposed to be concentrated on the improvement of physical education and sport program quality; to increase the number of schools organizing sport extra-curricular activities, sport units, and sport classes; to improve the quality of services and management of the Education and Training Center; and to increase the number of sports school in many region of provinces in Indonesia with national standard. If all those mentioned activities could be improved, then, this educational sports program will undoubtedly contribute positively to the sports development foundation in Indonesia generally. KEY WORD: Development of educational sports, recreational sport, and competitive sport, policy review, sports law, and sports development foundation in Indonesia.RINGKASAN: âPembangunan Olahraga Pendidikan di Indonesia: Studi Kebijakan Berdasarkan Undang-Undang Sistem Keolahragaan Nasionalâ. Undang-Undang Keolahragaan Nasional Tahun 2005 menyatakan bahwa ruang lingkup sistem olahraga di Indonesia dibagi menjadi tiga komponen, yaitu: Olahraga Pendidikan, Olahraga Rekreasi, dan Olahraga Prestasi. Suka atau tidak, masih ada bias dalam cara orang memberi arti olahraga dalam dokumen perencanaan, yang tidak relevan dengan makna sebenarnya didalam undang-undang; dan yang masih juga berarti bahwa olahraga harus diarahkan untuk mencapai prestasi puncak semata-mata. Ini jelas makna tidak akurat dalam arti yang sebenarnya dalam olahraga pendidikan, yang memiliki tujuan sendiri dan target berbeda, yakni memberikan anak-anak kesempatan yang lebih luas untuk mengeksplorasi potensi mereka dan mengembangkannya. Kebijakan untuk mengembangkan olahraga pendidikan seharusnya berkonsentrasi pada usaha untuk meningkatkan kualitas program pendidikan jasmani dan olahraga; untuk meningkatkan jumlah sekolah yang menyelenggarakan kegiatan olahraga ekstra-kurikuler, unit olahraga, dan kelas olahraga; untuk meningkatkan kualitas pelayanan dan pengelolaan Pusat Pendidikan dan Latihan; serta untuk meningkatkan jumlah sekolah olahraga di banyak wilayah provinsi di Indonesia dengan standar nasional. Jika semua kegiatan tersebut dapat ditingkatkan, maka program olahraga pendidikan ini pasti akan memberikan kontribusi positif bagi fondasi pembangunan olahraga di Indonesia pada umumnya.KATA KUNCI: Pembangunan olahraga pendidikan, olahraga rekreasi, olahraga prestasi, kajian kebijakan, undang-undang olahraga, dan fondasi pembangunan olahraga di Indonesia.About the Author: Dr. Amung Maâmun is a Senior Lecturer at the Department of Sports Education, Faculty of Sports and Health Education UPI (Indonesia University of Education), Jalan Dr. Setiabudhi No.229 Bandung 40154, West Java, Indonesia; and now is an Expert Staff for Information and Communication at the KEMENPORA RI (Ministry of Youth and Sports Affairs of the Republic of Indonesia) in Jakarta. The author can be contacted via e-mail at: amg_mamun@yahoo.co.idHow to cite this article? Maâmun, Amung. (2015). âDevelopment of the Educational Sport in Indonesia: The Policy Study Based on the Law of National Sports Systemâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.5(1) June, pp.33-48. Bandung, Indonesia: Minda Masagi Press and FPOK UPI Bandung, ISSN 2088-1290.Chronicle of the article: Accepted (March 24, 2015); Revised (May 24, 2015); and Published (June 30, 2015).